2006
DOI: 10.1111/j.1537-2995.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of skin disinfection method, deviation bag, and bacterial screening on clinical safety of platelet transfusions in the Netherlands

Abstract: The use of the diversion bag and, to a lesser extent, the use of double swabs with 70 percent isopropyl alcohol, led to a reduction of contamination. As expected, predominant contamination with resident skin bacteria was reduced. The combination of diversion bag and new disinfection led to a frequency of initial positive results for pooled five-donor PCs, which is similar to that of single-donor apheresis PCs. Furthermore, the bacterial detection system and associated product recall procedures have been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
202
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(220 citation statements)
references
References 24 publications
(65 reference statements)
12
202
1
5
Order By: Relevance
“…The spectrum of detected microorganisms derives predominantly, as expected, from the transient and resident skin flora and shows the limits of skin disinfection [3]. The microbial spectrum is comparable to that of other studies which also performed aerobic and anaerobic cultures [3,4,7].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The spectrum of detected microorganisms derives predominantly, as expected, from the transient and resident skin flora and shows the limits of skin disinfection [3]. The microbial spectrum is comparable to that of other studies which also performed aerobic and anaerobic cultures [3,4,7].…”
Section: Discussionsupporting
confidence: 81%
“…The microbial spectrum is comparable to that of other studies which also performed aerobic and anaerobic cultures [3,4,7]. The high proportion of PCs contaminated with Propionibacteria is striking, accounting for 54% of confirmed positive PCs and 46% of potentially positive PCs.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Screening of platelet preparations (PLTs) 2 for bacterial contamination by prospective culture testing has been implemented as part of the quality assurance program in several blood services. Despite screening of PLTs for bacterial contamination by culture, it has been demonstrated that there is still a substantial infection risk associated with transfusing PLTs, and septic complications have been observed in recipients, particularly with PLTs Ͼ4 days old (2)(3)(4)(5)(6)(7)(8)(9)(10). Early sampling strategies exhibit a high risk of sampling error, particularly when slow-growing bacteria are involved in the contamination.…”
mentioning
confidence: 99%